191k views
2 votes
Please help. 44 point's

Please help. 44 point's-example-1

1 Answer

4 votes

Answer:

  1. 25
  2. (5+4)*2 +6 -2*2 -1

Explanation:

1. Per the order of operations, do the exponentiation first, then the multiplication, then the addition:

= 6*7 -9*9 +64

= 42 -81 +64

= -39 +64

= 25

__

2. The expression given evaluates to ...

5 +4*2 +6 -2*2 -1 = 5 + 8 + 6 - 4 - 1 = 14

If you realize that the last three terms add to 1 and the first two terms can be rearranged to (5 +4)*2 = 18, then you can see that a sum of 19 is easily achievable. Parentheses are needed only around the first two numbers:

(5 +4)*2 +6 -2*2 -1 = 19

According to the order of operations, this is ...

9*2 +6 -2*2 -1 . . . . . operations inside parentheses are first

= 18 +6 -4 -1 . . . . . . multiplication is next

= 24 -4 -1 . . . . . . . . . sums are carried out left to right

= 20 -1

= 19

_____

The attachments show these expressions evaluated using the Google calculator. It can be relied upon to follow the order of operations exactly.

Please help. 44 point's-example-1
Please help. 44 point's-example-2
User Atinder
by
5.8k points